A study of the job description of library personnel of the College of Science Library, University of the Philippines Diliman - Gorospe, Ma. Judith Faye T. (2010)
Librarianship is a profession that is constantly changing. New tasks are emerging and other are becoming obsolete due to new technologies, which makes the importance of job descriptions emphasized now more than ever.